2019
DOI: 10.1136/bmjspcare-2019-001967
|View full text |Cite
|
Sign up to set email alerts
|

Primary palliative care for older people in three European countries: a mortality follow-back quality study

Abstract: background Many older people with serious chronic illnesses experience complex health problems for which palliative care is indicated. We aimed to examine the quality of primary palliative care for people aged 65-84 years and those 85 years and older who died non-suddenly in three European countries. Methods This is a nationwide representative mortality follow-back study. General practitioners (GPs) belonging to epidemiological surveillance networks in Belgium (BE), Italy (IT) and Spain (ES) (2013-2015) regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…However, although there is limited data on the service use of primary care by patients towards the end of life, existing studies indicate that there are considerable cross-country variations in both the quality and intensity of care, as well as room for improvement [12][13][14][15]. This identifies a need for more country-specific data on the use of primary care services by end of life cancer patients as an essential step to understanding and identifying gaps in service provision.…”
Section: Introductionmentioning
confidence: 99%
“…However, although there is limited data on the service use of primary care by patients towards the end of life, existing studies indicate that there are considerable cross-country variations in both the quality and intensity of care, as well as room for improvement [12][13][14][15]. This identifies a need for more country-specific data on the use of primary care services by end of life cancer patients as an essential step to understanding and identifying gaps in service provision.…”
Section: Introductionmentioning
confidence: 99%
“…Differences and inconsistencies in the provision of palliative care have been observed amongst European countries. 27,28 A European monitoring study showed that GPs had a proactive role in the delivery of primary palliative care in the Netherlands, whereas discussions regarding incurability of illness and life expectation took place significantly less often in Spain and Italy compared to Flanders and the Netherlands. 27 The identification of, and response to, training needs of GPs and the palliative care needs of patients needs to be adapted to their respective cultural, social, healthcare and spiritual contexts.…”
Section: Discussionmentioning
confidence: 99%
“…One concern is that without appropriate policy support, the available services may not be sufficiently accessible to older people. Continuous epidemiological monitoring of individual-level palliative care use 5,32 should follow any policy adjustments to evaluate whether they improve accessibility of services.…”
Section: Discussionmentioning
confidence: 99%